Simultaneous mitigation of arsenic and cadmium accumulation in rice (Oryza sativa L.) seedlings by silicon oxide nanoparticles under different water management schemes - Wang, Xiaoxuan; Jiang, Jiechao; Dou, Fugen; Sun, Wenjie; Ma, Xingmao (Paddy and water environment, 2021)
Arsenic (As) and cadmium (Cd) accumulation in rice is a great food safety concern. Simultaneous control of As and Cd accumulation in rice grown in co-contaminated rice paddies is highly desirable but difficult to achieve. Silicon oxide nanoparticles (SiO 2 NPs) were shown to lower plant As and Cd accumulation in rice tissues separately, raising the possibility that SiO 2 NPs may concurrently decrease both As and Cd in rice tissues in a co-contaminated soil. Due to the remarkable effect of water management, this study aimed at investigating the effects of SiO 2 NPs on the uptake of As and Cd by rice seedlings under both continuous flooding (CF) and alternate wetting and drying (AWD) conditions. Pot experiments were conducted by exposing rice seedlings to soils containing 5 mg/kg As and 1 mg/kg Cd, and 0, 150, 500 or 2,000 mg/kg of SiO 2 NPs for 14 days. SiO 2 NPs displayed significant impact on plant As and Cd uptake and the net effect depended on the concentration of SiO 2 NPs and water management schemes. Significantly, simultaneous reduction of As and Cd in rice shoots was observed at 500 mg/kg SiO 2 NPs under AWD irrigation, in which SiO 2 NPs reduced As and Cd in rice shoots by 29% and 68%, respectively, compared with seedlings exposed to As and Cd only at the same irrigation condition. Rice shoots contained approximately 70% and 50% less As and Cd under AWD than CF irrigation with 500 mg/kg SiO 2 NPs addition, suggesting a strong interaction between SiO 2 NPs and water irrigation scheme. Graphic abstract